Nutritional and Physicochemical Properties and Safe Consumption of Jackfruit Seeds (Artocarpus heterophyllus Lam.) - Celestial, Macey Kate Jimenez; Sagum, Rosario delos Santos; Trinidad, Trinidad (International Journal on Food, Agriculture and Natural Resources, 2023)
Fruits and vegetable by-products such as peels, rinds, and seeds are the focus of functional food research. By-products from jackfruit like seeds are functional foods/ingredients. However, studies on jackfruit seeds’ nutritional, physicochemical properties and safe consumption are limited. Thus, this study aimed to determine the nutritional and physicochemical properties of raw, roasted, and boiled jackfruit seeds, as well as how these seeds could be safely consumed. The nutrient composition, total dietary fiber composition and fermentability, resistant starch, antinutrients, heavy metals, and microbial load were determined using standard methods. Jackfruit seeds are good source of protein (9.9–10.2g/100g), ash (3.3–3.8g/100g), carbohydrates (21.45–82.15g/100g), a high source of dietary fiber (12.11–13.83g/100g), resistant starch (19.9–25.6g/100g) and amylose (20.61–23.03g/100g). Phytic acid, tannic acid, heavy metals, and microbial parameters of raw and thermally processed jackfruit seed were within acceptable limits, except for the microbial parameters in raw seeds. The starchy structure of processed jackfruit seed expands its granules with increased surface area, leading to better digestion. In conclusion, processed jackfruit seed can be a potential functional food or ingredient. Consumers and food industry professionals should be aware of the beneficial effects of jackfruit by-products.